No steel pipes

JP2026170819APending Publication Date: 2026-10-22NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025064649
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-22

AI Technical Summary

Benefits of technology

【0015】 本開示による継目無鋼管は、高強度と、優れた耐水素脆化特性とを有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026170819000001
    Figure 2026170819000001
  • Figure 2026170819000002
    Figure 2026170819000002
  • Figure 2026170819000003
    Figure 2026170819000003
Patent Text Reader

Abstract

To provide seamless steel pipes with high strength and excellent resistance to hydrogen embrittlement. [Solution] The seamless steel pipe according to this disclosure has a chemical composition in mass%, of C: 0.15~0.45%, Si: 0.05~1.00%, Mn: 0.05~0.50%, P: 0.030% or less, S: 0.0050% or less, Cr: 0.30~1.20%, Mo: 0.50~2.00%, Ti: 0.002~0.020%, Nb: 0.002~0.100% The composition is as follows: V: 0.05~0.30%, B: 0.0005~0.0040%, Al: 0.005~0.100%, N: 0.0100% or less, O: less than 0.0040%, and the remainder is Fe and impurities, with a tensile strength of 900~1180 MPa, and in a seamless steel pipe, the number density of Al oxide particles with a major diameter of 5.0 μm or more is 40 particles / 200 mm. 2 The residual stress is less than -50 MPa on the inner surface of the seamless steel pipe.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to seamless steel pipes, and more particularly to seamless steel pipes used in sour environments and seamless steel pipes used in high-pressure hydrogen containers. [Background technology]

[0002] Some oil wells and gas wells (hereinafter collectively referred to as "oil wells") contain environments with a high concentration of corrosive substances. These corrosive substances include, for example, corrosive gases such as hydrogen sulfide. In this specification, an environment containing hydrogen sulfide is referred to as a "sour environment." The temperature of a sour environment varies depending on the depth of the well, but is generally between room temperature and approximately 200°C.

[0003] Examples of steel materials used in such sour environments include oil well pipes and line pipes. Furthermore, seamless steel pipes are sometimes used for these oil well pipes. Seamless steel pipes have superior corrosion resistance and compressive strength compared to welded steel pipes.

[0004] On the other hand, when seamless steel pipes are used in a sour environment, the surface of the seamless steel pipe comes into contact with corrosive substances, causing an electrochemical reaction and generating hydrogen. Due to this hydrogen, seamless steel pipes are prone to hydrogen embrittlement cracking, typified by sulfide stress cracking (SSC). Therefore, seamless steel pipes used in a sour environment require excellent resistance to hydrogen embrittlement.

[0005] Techniques for improving hydrogen embrittlement resistance in steel materials used in sour environments are disclosed in Japanese Patent Publication No. 2011-246798 (Patent Document 1) and Japanese Patent Publication No. 2015-38247 (Patent Document 2).

[0006] The steel material disclosed in Patent Document 1 is a high-strength seamless steel pipe for oil wells made of low-alloy steel, which secures a predetermined amount of solute Mo, refines prior austenite grains, and disperses M2C type precipitates. In this way, the SSC resistance of the steel material is enhanced. The steel material disclosed in Patent Document 1 further segregates Mo on the prior austenite grain boundaries to further enhance the hydrogen embrittlement resistance.

[0007] The steel material disclosed in Patent Document 2 is a high-strength seamless steel pipe for oil wells made of low-alloy steel, which enhances hydrogen embrittlement resistance by forming a Mo segregation region.

[0008] More recently, development of fuel cell vehicles that run on hydrogen as fuel and practical implementation of hydrogen stations that supply hydrogen to fuel cell vehicles have been progressing. High-pressure hydrogen gas is stored in the high-pressure hydrogen accumulator installed in the hydrogen station. In addition, development of vehicles equipped with high-pressure hydrogen cylinders as fuel cell vehicles is also progressing. Steel materials used for high-pressure hydrogen containers represented by such high-pressure hydrogen accumulators and high-pressure hydrogen cylinders are also required to have excellent hydrogen embrittlement resistance.

[0009] A technique for enhancing hydrogen embrittlement resistance in steel materials used for high-pressure hydrogen containers is proposed in Japanese Unexamined Patent Application Publication No. 2009-74122 (Patent Document 3). The steel material disclosed in Patent Document 3 is a low-alloy steel for high-pressure hydrogen gas environments, in which the V content and Mo content are increased more than in conventional cases to improve the morphology of carbides at prior austenite grain boundaries, thereby enhancing hydrogen embrittlement resistance. [Prior Art Documents] [Patent Documents]

[0010] [Patent Document 1] Japanese Unexamined Patent Application Publication No. 2011-246798 [Patent Document 2] Japanese Unexamined Patent Application Publication No. 2015-38247 [Patent Document 3] Japanese Unexamined Patent Application Publication No. 2009-74122 [Patent Document 4] Japanese Patent Publication No. 2015-184118 [Overview of the project] [Problems that the invention aims to solve]

[0011] The technologies disclosed in the above-mentioned Patent Documents 1 to 3 can improve the hydrogen embrittlement resistance of steel materials intended for use in sour environments or as high-pressure hydrogen containers. However, seamless steel pipes with excellent hydrogen embrittlement resistance may be obtained by means other than those described in the above-mentioned Patent Documents 1 to 3.

[0012] Furthermore, steel materials intended for use in sour environments or for high-pressure hydrogen containers require a certain level of strength. In recent years, with the increasing use of deep wells in oil wells, seamless steel pipes for oil wells intended for use in sour environments are required to be stronger. Similarly, seamless steel pipes for high-pressure hydrogen containers, intended for use in such containers, are also required to be stronger to meet the demand for thinner walls. In short, seamless steel pipes intended for use in sour environments or for high-pressure hydrogen containers are required to possess both high strength and excellent resistance to hydrogen embrittlement.

[0013] The purpose of this disclosure is to provide a seamless steel pipe having high strength and excellent resistance to hydrogen embrittlement. [Means for solving the problem]

[0014] The seamless steel pipes described herein are The chemical composition is expressed in mass percent. C: 0.15~0.45%, Si: 0.05~1.00%, Mn: 0.05~0.50%, P:0.030% or less, S: 0.0050% or less, Cr: 0.30~1.20%, Mo: 0.50~2.00%, Ti: 0.002~0.020%, Nb: 0.002~0.100%, V: 0.05~0.30%, B: 0.0005~0.0040%, Al: 0.005~0.100%, N: 0.0100% or less, O: Less than 0.0040%, Cu: 0~0.50%, Ni: 0~0.50%, W: 0~0.50%, Zr: 0~0.0100%, Ca: 0~0.0100%, Mg: 0~0.0100%, Rare earth elements: 0-0.0100%, and, The remainder consists of Fe and impurities. The tensile strength is 900-1180 MPa. In the aforementioned seamless steel pipe, In mass%, the Al content is 20% or more, the O content is 10% or more, and the number density of Al oxide particles with a major axis of 5.0 μm or more is 40 particles / 200 mm 2 It is less than, The residual stress on the inner surface of the seamless steel pipe is -50 MPa or less. [Effects of the Invention]

[0015] The seamless steel pipe according to this disclosure has high strength and excellent resistance to hydrogen embrittlement. [Modes for carrying out the invention]

[0016] The inventors first considered obtaining a seamless steel pipe with a high tensile strength of 900 to 1180 MPa, anticipating its use in sour environments and as a high-pressure hydrogen container. In other words, the inventors investigated and examined methods to improve the hydrogen embrittlement resistance of a seamless steel pipe intended for use in sour environments and as a high-pressure hydrogen container, even if its tensile strength is 900 to 1180 MPa. As a result, the inventors obtained the following findings.

[0017] Next, the inventors focused on the chemical composition and investigated a seamless steel pipe that achieves both a tensile strength of 900-1180 MPa and excellent hydrogen embrittlement resistance. Specifically, the inventors considered the following composition by mass%, C: 0.15-0.45%, Si: 0.05-1.00%, Mn: 0.05-0.50%, P: 0.030% or less, S: 0.0050% or less, Cr: 0.30-1.20%, Mo: 0.50-2.00%, Ti: 0.002-0.020%, Nb: 0.002-0.100%, V: 0.05-0.30%, B: 0.0005-0.0040%, Al: 0.005-0.100%, N: 0 We considered that a seamless steel pipe having a chemical composition of less than 0.0100%, less than 0.0040% O, 0-0.50% Cu, 0-0.50% Ni, 0-0.50% W, 0-0.50% Zr, 0-0.0100% Ca, 0-0.0100% Mg, 0-0.0100% rare earth elements, and the remainder being Fe and impurities, could potentially achieve both a tensile strength of 900-1180 MPa and excellent resistance to hydrogen embrittlement.

[0018] On the other hand, even with seamless steel pipes having the above-mentioned chemical composition, excellent hydrogen embrittlement resistance was sometimes not obtained when the tensile strength was 900 to 1180 MPa. Therefore, the inventors of the present invention investigated in detail a method to improve the hydrogen embrittlement resistance of seamless steel pipes having the above-mentioned chemical composition while maintaining the tensile strength. As a result, the following findings were obtained.

[0019] First, it was found that in seamless steel pipes having the above-mentioned chemical composition and a tensile strength of 900-1180 MPa, the hydrogen embrittlement resistance decreases when a large number of coarse Al oxide particles with a major diameter of 5.0 μm or more are formed. Here, Al oxide is a hard oxide, and there is a large difference in hardness between it and the base material. Therefore, coarse Al oxide particles tend to become crack pathways at the interface with the base material. Furthermore, this effect may be particularly evident in a hydrogen environment. Here, in this specification, particles with an Al content of 20% or more by mass and an O content of 10% or more are also referred to as "Al oxide". In this specification, Al oxide particles with a major diameter of 5.0 μm or more are also referred to as "coarse Al oxide".

[0020] As a result of detailed studies by the inventors, a seamless steel pipe having the above-mentioned chemical composition and a tensile strength of 900-1180 MPa has a number density of 40 coarse Al oxides / 200 mm 2 It has become clear that if the value is less than the above, the hydrogen embrittlement resistance can be improved, provided that the other components of this embodiment are satisfied. Therefore, in the seamless steel pipe according to this embodiment, assuming the above chemical composition and a tensile strength of 900 to 1180 MPa, the number density of coarse Al oxide is set to 40 particles / 200 mm 2 Less than.

[0021] On the other hand, having the above chemical composition, the number density of coarse Al oxide is 40 particles / 200 mm 2 Even with seamless steel pipes of less than 100 MPa, if they have a tensile strength of 900 to 1180 MPa, it was sometimes not possible to obtain stable and excellent hydrogen embrittlement resistance. Therefore, the inventors have developed a material having the above-mentioned chemical composition and a tensile strength of 900 to 1180 MPa, with a number density of 40 coarse Al oxides per 200 mm 2 For seamless steel pipes of less than [amount missing], various methods were investigated to stably obtain excellent hydrogen embrittlement resistance.

[0022] As a result of further detailed studies by the inventors, the above-mentioned chemical composition and tensile strength of 900-1180 MPa, with a number density of 40 coarse Al oxides / 200 mm² are obtained. 2 For seamless steel pipes of less than -50 MPa, it has become clear that hydrogen embrittlement resistance can be stably enhanced if the residual stress on the inner surface of the seamless steel pipe is -50 MPa or less. Therefore, the seamless steel pipe according to this embodiment has the above-mentioned chemical composition and a tensile strength of 900 to 1180 MPa, and a number density of coarse Al oxide of 40 particles / 200 mm 2 Assuming that the residual stress on the inner surface of the seamless steel pipe is less than -50 MPa, the seamless steel pipe according to this embodiment can achieve both a tensile strength of 900 to 1180 MPa and excellent resistance to hydrogen embrittlement.

[0023] Furthermore, it has the above-mentioned chemical composition and a tensile strength of 900-1180 MPa, and the number density of coarse Al oxide is 40 particles / 200 mm 2In a seamless steel pipe of less than the specified value, the reason why the hydrogen embrittlement resistance can be stably enhanced when the residual stress on the inner surface of the seamless steel pipe is -50MPa or less has not been clarified in detail. However, the present inventors infer as follows.

[0024] As described above, in the seamless steel pipe according to the present embodiment, the number density of coarse Al oxides that easily form a crack path is set to 40 pieces / 200mm 2 is reduced to less than that value. On the other hand, in a hydrogen environment, minute flaws and the like may also serve as crack initiation points, and there is a concern that cracks may propagate. That is, if crack propagation can be further suppressed, the hydrogen embrittlement resistance of the seamless steel pipe may be improved. Here, when the residual stress on the inner surface of the seamless steel pipe shows a large negative value of -50MPa or less, compressive residual stress is generated in the vicinity of the inner surface of the seamless steel pipe. Furthermore, the compressive residual stress suppresses the opening of cracks, thereby suppressing crack propagation.

[0025] In addition, when compressive residual stress is generated in a part of the interior of the seamless steel pipe, a region where tensile residual stress is generated is also formed due to the balance of internal stresses. Here, it is also considered that crack propagation is promoted in the region where tensile residual stress is generated. On the other hand, when strong compressive residual stress of -50MPa or less is generated inside the seamless steel pipe, under the influence of the region where this compressive residual stress is generated, crack propagation may be suppressed in the entire seamless steel pipe. As a result, the present inventors infer that crack propagation is suppressed and the hydrogen embrittlement resistance can be enhanced.

[0026] Through the above mechanism, the present inventors infer that the seamless steel pipe according to the present embodiment can achieve both a tensile strength of 900 to 1180 MPa and excellent hydrogen embrittlement resistance. Here, by a mechanism other than the above-mentioned mechanism, the seamless steel pipe having the above-mentioned chemical composition and a tensile strength of 900 to 1180 MPa, and having a number density of coarse Al oxides of 40 pieces / 200mm 2In seamless steel pipes of less than -50 MPa, it may be possible to improve hydrogen embrittlement resistance by reducing the residual stress on the inner surface to -50 MPa or less. However, having the above-mentioned chemical composition and a tensile strength of 900-1180 MPa, and a number density of coarse Al oxide of 40 particles / 200 mm 2 The fact that seamless steel pipes with a residual stress of -50 MPa or less on the inner surface have excellent hydrogen embrittlement resistance has been demonstrated by the examples described later.

[0027] Based on the above findings, the gist of the seamless steel pipe according to this embodiment is as follows:

[0028] [1] It is a seamless steel pipe, The chemical composition is expressed in mass percent. C: 0.15~0.45%, Si: 0.05~1.00%, Mn: 0.05~0.50%, P:0.030% or less, S: 0.0050% or less, Cr: 0.30~1.20%, Mo: 0.50~2.00%, Ti: 0.002~0.020%, Nb: 0.002~0.100%, V: 0.05~0.30%, B: 0.0005~0.0040%, Al: 0.005~0.100%, N: 0.0100% or less, O: Less than 0.0040%, Cu: 0~0.50%, Ni: 0~0.50%, W: 0~0.50%, Zr: 0~0.0100%, Ca: 0~0.0100%, Mg: 0~0.0100%, Rare earth elements: 0-0.0100%, and, The remainder consists of Fe and impurities. The tensile strength is 900-1180 MPa. In the aforementioned seamless steel pipe, In mass%, the Al content is 20% or more, the O content is 10% or more, and the number density of Al oxide particles with a major axis of 5.0 μm or more is 40 particles / 200 mm 2 It is less than, The residual stress on the inner surface of the aforementioned seamless steel pipe is -50 MPa or less. Seamless steel pipe.

[0029] [2] [1] A seamless steel pipe as described above, The aforementioned chemical composition is Cu: 0.01~0.50%, Ni: 0.01~0.50%, W: 0.01~0.50%, Zr: 0.0001~0.0100%, Ca: 0.0001~0.0100%, Mg: 0.0001~0.0100%, and, Contains one or more elements selected from the group consisting of rare earth elements: 0.0001 to 0.0100%. Seamless steel pipe.

[0030] [3] A seamless steel pipe as described in [1] or [2], The aforementioned seamless steel pipe is one of the following: a seamless steel pipe for oil wells, a seamless steel pipe for line pipes, or a seamless steel pipe for high-pressure hydrogen containers. Seamless steel pipe.

[0031] [4] [3] A seamless steel pipe as described above, The seamless steel pipe for high-pressure hydrogen containers is either a seamless steel pipe for high-pressure hydrogen accumulators or a seamless steel pipe for high-pressure hydrogen cylinders. Seamless steel pipe.

[0032] In this specification, "seamless steel pipe for oil wells" means a seamless steel pipe used as an oil well pipe. Oil well pipe refers to the general term for casings, tubing, and drill pipes used in drilling oil or gas wells, extracting crude oil or natural gas, etc.

[0033] In this specification, "seamless steel pipe for line pipe" means a seamless steel pipe used as a line pipe in a pipeline that transports production fluid (crude oil or natural gas) extracted from an oil well or gas well. Pipelines include, for example, flow lines that transport production fluid from an oil well or gas well, gathering lines that collect the production fluid transported by the flow line and transport it to a primary processing facility, trunk lines that transport the production fluid, which has undergone primary processing such as dewatering, to the vicinity of the market, and distribution lines that transport it to consumers.

[0034] In this specification, "seamless steel pipe for high-pressure hydrogen containers" refers to seamless steel pipes used in high-pressure hydrogen containers for storing high-pressure hydrogen gas, as standardized in ISO 11439, ANSI / NGV, the High-Pressure Gas Safety Act, the Container Safety Regulations Exemplary Standards, etc. High-pressure hydrogen containers include, for example, high-pressure hydrogen accumulators installed at hydrogen stations and high-pressure hydrogen cylinders mounted on fuel cell vehicles.

[0035] The seamless steel pipe according to this embodiment will be described in detail below. Unless otherwise specified, the "%" in relation to elements refers to mass percentage. Also, in the following description, the seamless steel pipe will be simply referred to as "steel material".

[0036] [Chemical composition] The chemical composition of the seamless steel pipe according to this embodiment contains the following elements:

[0037] C: 0.15~0.45% Carbon (C) enhances hardenability and makes the microstructure of the steel primarily composed of tempered martensite and tempered bainite. As a result, the hydrogen embrittlement resistance of the steel is improved. Furthermore, C forms carbides or carbonitrides, increasing the strength of the steel. If the C content is too low, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the C content is too high, even if the content of other elements is within the range of this embodiment, there will be an excessive amount of carbides in the steel, and the hydrogen embrittlement resistance of the steel will decrease. Therefore, the C content is 0.15 to 0.45%. The preferred lower limit of the C content is 0.18%, more preferably 0.20%, even more preferably 0.22%, and even more preferably 0.24%. The preferred upper limit of the C content is 0.40%, more preferably 0.38%, and even more preferably 0.35%.

[0038] Si: 0.05~1.00% Silicon (Si) deoxidizes steel and reduces inclusions in the steel material. As a result, the hydrogen embrittlement resistance of the steel material is improved. If the Si content is too low, the above effect cannot be fully obtained even if the content of other elements is within the range of this embodiment. On the other hand, if the Si content is too high, the hydrogen embrittlement resistance of the steel material will decrease even if the content of other elements is within the range of this embodiment. Therefore, the Si content is 0.05 to 1.00%. The preferred lower limit of the Si content is 0.08%, more preferably 0.10%, even more preferably 0.15%, and still more preferably 0.20%. The preferred upper limit of the Si content is 0.85%, more preferably 0.70%, even more preferably 0.60%, even more preferably 0.50%, even more preferably 0.45%, even more preferably 0.40%, and still more preferably 0.35%.

[0039] Mn: 0.05~0.50% Manganese (Mn) deoxidizes steel. Mn further enhances hardenability and improves the hydrogen embrittlement resistance of the steel. If the Mn content is too low, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Mn content is too high, even if the content of other elements is within the range of this embodiment, a large number of sulfides will be formed, and the hydrogen embrittlement resistance of the steel will decrease. Therefore, the Mn content is 0.05 to 0.50%. The preferred lower limit of the Mn content is 0.06%, and more preferably 0.08%. The preferred upper limit of the Mn content is 0.48%, and more preferably 0.45%.

[0040] P:0.030% or less Phosphorus (P) is an unavoidable impurity. In other words, the lower limit of the P content is greater than 0%. If the P content is too high, even if the content of other elements is within the range of this embodiment, P will segregate at the grain boundaries, reducing the hydrogen embrittlement resistance of the steel. Therefore, the P content is 0.030% or less. It is preferable to have as low a P content as possible. However, an extreme reduction in the P content significantly increases manufacturing costs. Therefore, considering industrial production, the preferred lower limit of the P content is 0.001%, more preferably 0.003%, and even more preferably 0.005%. The preferred upper limit of the P content is 0.028%, even more preferably 0.025%, even more preferably 0.020%, even more preferably 0.015%, and even more preferably 0.010%.

[0041] S: 0.0050% or less Sulfur (S) is an unavoidable impurity. That is, the lower limit of the S content is greater than 0%. If the S content is too high, even if the content of other elements is within the range of this embodiment, S will segregate at the grain boundaries, reducing the hydrogen embrittlement resistance of the steel. Therefore, the S content is 0.0050% or less. It is preferable to have as low an S content as possible. However, an extreme reduction in the S content significantly increases manufacturing costs. Therefore, considering industrial production, the preferred lower limit of the S content is 0.0001%, more preferably 0.0003%, even more preferably 0.0005%, and even more preferably 0.0008%. The preferred upper limit of the S content is 0.0040%, more preferably 0.0030%, even more preferably 0.0025%, and even more preferably 0.0020%.

[0042] Cr: 0.30~1.20% Chromium (Cr) enhances the hardenability of steel and improves its resistance to hydrogen embrittlement. Furthermore, Cr increases the tempering softening resistance of steel, enabling high-temperature tempering. As a result, the hydrogen embrittlement resistance of steel is improved. If the Cr content is too low, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Cr content is too high, even if the content of other elements is within the range of this embodiment, coarse carbides will be formed, and the hydrogen embrittlement resistance of steel will decrease. Therefore, the Cr content is 0.30 to 1.20%. The preferred lower limit of the Cr content is 0.35%, more preferably 0.40%, even more preferably 0.50%, and even more preferably 0.60%. The preferred upper limit of the Cr content is 1.18%, more preferably 1.15%, and even more preferably 1.10%.

[0043] Mo: 0.50~2.00% Molybdenum (Mo) enhances the hardenability of steel and improves its resistance to hydrogen embrittlement. Mo further increases the tempering softening resistance of steel, enabling high-temperature tempering. As a result, the hydrogen embrittlement resistance of steel is improved. Mo further strengthens prior γ grain boundaries, improving the hydrogen embrittlement resistance of steel. If the Mo content is too low, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Mo content is too high, even if the content of other elements is within the range of this embodiment, coarse carbides are formed, and the hydrogen embrittlement resistance of steel decreases. Therefore, the Mo content is 0.50 to 2.00%. The preferred lower limit of the Mo content is 0.52%, more preferably 0.55%, and even more preferably 0.60%. The preferred upper limit of the Mo content is 1.80%, more preferably 1.60%, even more preferably 1.40%, and even more preferably 1.25%.

[0044] Ti: 0.002~0.020% Titanium (Ti) forms fine precipitates and refines the crystal grains through a pinning effect, thereby improving the hydrogen embrittlement resistance of steel. If the Ti content is too low, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Ti content is too high, coarse Ti nitrides will be formed, even if the content of other elements is within the range of this embodiment. Coarse Ti nitrides become the initiation point for cracks. As a result, the hydrogen embrittlement resistance of steel decreases. Therefore, the Ti content is 0.002 to 0.020%. The preferred lower limit of the Ti content is 0.003%, more preferably 0.004%. The preferred upper limit of the Ti content is 0.018%, more preferably 0.017%, and even more preferably 0.015%.

[0045] Nb: 0.002~0.100% Niobium (Nb) forms carbides, nitrides, or carbonitrides (hereinafter referred to as "carbonitrides, etc.") and refines the prior γ grains through a pinning effect, thereby improving the hydrogen embrittlement resistance of the steel. Furthermore, Nb forms fine carbides during tempering, increasing the tempering softening resistance of the steel and improving its strength. If the Nb content is too low, the above effects cannot be fully obtained even if the content of other elements is within the range of this embodiment. On the other hand, if the Nb content is too high, even if the content of other elements is within the range of this embodiment, an excessive amount of carbonitrides, etc. will be generated, and the hydrogen embrittlement resistance of the steel will actually decrease. Therefore, the Nb content is 0.002 to 0.100%. The preferred lower limit of the Nb content is 0.005%, more preferably 0.010%, even more preferably 0.015%, and even more preferably 0.020%. The preferred upper limit for the Nb content is 0.080%, more preferably 0.060%, even more preferably 0.050%, and even more preferably 0.040%.

[0046] V: 0.05~0.30% Vanadium (V) forms carbonitrides and other compounds, thereby enhancing the hydrogen embrittlement resistance of steel. If the V content is too low, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the V content is too high, even if the content of other elements is within the range of this embodiment, carbonitrides and other compounds will be excessively formed, reducing the hydrogen embrittlement resistance of steel. Therefore, the V content is 0.05 to 0.30%. The preferred lower limit of the V content is 0.06%, more preferably 0.08%. The preferred upper limit of the V content is 0.25%, more preferably 0.20%, and even more preferably 0.15%.

[0047] B: 0.0005~0.0040% Boron (B) enhances the hardenability of steel and improves its resistance to hydrogen embrittlement. If the B content is too low, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the B content is too high, even if the content of other elements is within the range of this embodiment, coarse B nitrides may be formed, which can become the initiation point for cracks. As a result, the resistance to hydrogen embrittlement of the steel decreases. Therefore, the B content is 0.0005 to 0.0040%. The preferred lower limit of the B content is 0.0006%, more preferably 0.0008%, and even more preferably 0.0010%. The preferred upper limit of the B content is 0.0030%, more preferably 0.0025%, and even more preferably 0.0020%.

[0048] Al: 0.005~0.100% Aluminum (Al) deoxidizes steel. Al further forms nitrides and refines the crystal grains through a pinning effect, thereby improving the hydrogen embrittlement resistance of the steel. If the Al content is too low, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Al content is too high, even if the content of other elements is within the range of this embodiment, a large number of coarse Al oxides will be formed, and the hydrogen embrittlement resistance of the steel will decrease. Therefore, the Al content is 0.005 to 0.100%. The preferred lower limit of the Al content is 0.010%, more preferably 0.020%, and even more preferably 0.025%. The preferred upper limit of the Al content is 0.080%, more preferably 0.060%, even more preferably 0.050%, and even more preferably 0.045%. In this specification, "Al" content refers to "acid-soluble Al," that is, the content of "sol.Al."

[0049] N: 0.0100% or less Nitrogen (N) is inevitably present. That is, the lower limit of the N content is greater than 0%. N forms nitrides, which refine the crystal grains through a pinning effect, thereby improving the hydrogen embrittlement resistance of the steel. On the other hand, if the N content is too high, even if the content of other elements is within the range of this embodiment, coarse nitrides will be formed, and the hydrogen embrittlement resistance of the steel will decrease. Therefore, the N content is 0.0100% or less. A preferred lower limit for the N content to more effectively obtain the above effect is 0.0001%, more preferably 0.0005%, even more preferably 0.0010%, even more preferably 0.0020%, and even more preferably 0.0025%. A preferred upper limit for the N content is 0.0080%, more preferably 0.0060%, and even more preferably 0.0055%.

[0050] O: Less than 0.0040% Oxygen (O) is an unavoidable impurity. Therefore, the lower limit of the O content is greater than 0%. If the O content is too high, even if the content of other elements is within the range of this embodiment, coarse oxides will be formed, and the hydrogen embrittlement resistance of the steel will decrease. Therefore, the O content is less than 0.0040%. It is preferable that the O content be as low as possible. However, an extreme reduction in the O content significantly increases manufacturing costs. Therefore, considering industrial production, the preferred lower limit of the O content is 0.0001%, more preferably 0.0003%, and even more preferably 0.0005%. The preferred upper limit of the O content is 0.0039%, more preferably 0.0035%, and even more preferably 0.0030%.

[0051] The remainder of the chemical composition of the seamless steel pipe according to this embodiment consists of Fe and impurities. Here, impurities in the chemical composition refer to substances that are introduced during the industrial manufacture of the seamless steel pipe from raw materials such as ore, scrap, or the manufacturing environment, and are not intentionally included, but are acceptable within a range that does not adversely affect the seamless steel pipe according to this embodiment.

[0052] [Optional element] The chemical composition of the seamless steel pipe according to this embodiment may further contain one or more elements selected from the group consisting of Cu and Ni in place of a portion of Fe. Any of these elements are optional and may not be included. If included, Cu and Ni enhance the hardenability of the steel and improve its resistance to hydrogen embrittlement.

[0053] Cu: 0~0.50% Copper (Cu) is an optional element and may not be included. In other words, the Cu content may be 0%. When included, Cu improves the hardenability of the steel and enhances its resistance to hydrogen embrittlement. Even a small amount of Cu can provide some of the above effects. However, if the Cu content is too high, the hot workability of the steel will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the Cu content is 0 to 0.50%. The preferred lower limit of the Cu content is 0.01%, more preferably 0.05%. The preferred upper limit of the Cu content is 0.40%, more preferably 0.30%, even more preferably 0.20%, even more preferably 0.10%, and even more preferably 0.08%.

[0054] Ni: 0~0.50% Nickel (Ni) is an optional element and may not be included. In other words, the Ni content may be 0%. When included, Ni improves the hardenability of the steel and enhances its resistance to hydrogen embrittlement. Even a small amount of Ni will provide some of the above effects. However, if the Ni content is too high, the manufacturing cost will increase drastically, even if the content of other elements is within the range of this embodiment. Therefore, the Ni content is 0 to 0.50%. The preferred lower limit of the Ni content is 0.01%, more preferably 0.05%. The preferred upper limit of the Ni content is 0.40%, more preferably 0.30%, even more preferably 0.20%, even more preferably 0.10%, and even more preferably 0.08%.

[0055] The chemical composition of the seamless steel pipe according to this embodiment may further contain one or more elements selected from the group consisting of W and Zr in place of a portion of Fe. Any of these elements are optional and may not be included. If included, W and Zr form fine carbides, thereby increasing the strength of the steel material.

[0056] W: 0~0.50% Tungsten (W) is an optional element and may not be included. That is, the W content may be 0%. When included, W forms fine carbides, increasing the strength of the steel. Even a small amount of W can provide the above effect to some extent. However, if the W content is too high, even if the content of other elements is within the range of this embodiment, coarse carbides will be formed, reducing the steel's resistance to SSC (Steel-Sealing Carbon). Therefore, the W content is 0 to 0.50%. The preferred lower limit of the W content is 0.01%, more preferably 0.05%, and even more preferably 0.08%. The preferred upper limit of the W content is 0.40%, more preferably 0.30%, even more preferably 0.20%, even more preferably 0.10%, and even more preferably 0.08%.

[0057] Zr: 0~0.0100% Zirconium (Zr) is an optional element and may not be present. That is, the Zr content may be 0%. When present, Zr forms fine carbides, increasing the strength of the steel. Even a small amount of Zr will provide some degree of the above effect. However, if the Zr content is too high, even if the content of other elements is within the range of this embodiment, coarse oxides will be formed, reducing the steel's resistance to SSC (Steel-Sealing Carbon). Therefore, the Zr content is 0 to 0.0100%. The preferred lower limit of the Zr content is 0.0001%, more preferably 0.0003%, and even more preferably 0.0006%. The preferred upper limit of the Zr content is 0.0080%, more preferably 0.0060%, even more preferably 0.0040%, even more preferably 0.0020%, and even more preferably 0.0018%.

[0058] The chemical composition of the seamless steel pipe according to this embodiment may further contain one or more elements selected from the group consisting of Ca, Mg, and rare earth elements (REM) in place of a portion of Fe. Any of these elements are optional and may not be included. If included, Ca, Mg, and rare earth elements (REM) enhance the hydrogen embrittlement resistance of the steel material.

[0059] Ca: 0~0.0100% Calcium (Ca) is an optional element and may not be present. In other words, the Ca content may be 0%. If present, Ca forms sulfides with S in the steel, improving the hydrogen embrittlement resistance of the steel. Even a small amount of Ca can provide some of the above effect. However, if the Ca content is too high, even if the content of other elements is within the range of this embodiment, the oxides in the steel will coarseen, reducing the hydrogen embrittlement resistance of the steel. Therefore, the Ca content is 0 to 0.0100%. The preferred lower limit of the Ca content is 0.0001%, more preferably 0.0003%, even more preferably 0.0006%, and still more preferably 0.0010%. The preferred upper limit of the Ca content is 0.0080%, more preferably 0.0060%, even more preferably 0.0040%, even more preferably 0.0030%, even more preferably 0.0020%, and still more preferably 0.0018%.

[0060] Mg: 0~0.0100% Magnesium (Mg) is an optional element and may not be present. In other words, the Mg content may be 0%. If present, Mg forms sulfides with S in the steel, improving the hydrogen embrittlement resistance of the steel. Even a small amount of Mg can provide the above effect to some extent. However, if the Mg content is too high, even if the content of other elements is within the range of this embodiment, the oxides in the steel will coarseen, reducing the hydrogen embrittlement resistance of the steel. Therefore, the Mg content is 0 to 0.0100%. The preferred lower limit of the Mg content is 0.0001%, more preferably 0.0003%, even more preferably 0.0006%, and still more preferably 0.0010%. The preferred upper limit of the Mg content is 0.0080%, more preferably 0.0060%, even more preferably 0.0040%, even more preferably 0.0030%, even more preferably 0.0020%, and still more preferably 0.0018%.

[0061] Rare earth elements (REM): 0~0.0100% Rare earth elements (REMs) are optional and may not be present. In other words, the REM content may be 0%. If present, REMs form sulfides with sulfur in the steel, improving the hydrogen embrittlement resistance of the steel. Even a small amount of REM can provide some of the above effect. However, if the REM content is too high, even if the content of other elements is within the range of this embodiment, the oxides in the steel will coarseen, reducing the hydrogen embrittlement resistance of the steel. Therefore, the REM content is 0 to 0.0100%. The preferred lower limit of the REM content is 0.0001%, more preferably 0.0003%, even more preferably 0.0006%, and still more preferably 0.0010%. The preferred upper limit of the REM content is 0.0080%, more preferably 0.0060%, even more preferably 0.0040%, even more preferably 0.0030%, even more preferably 0.0020%, and still more preferably 0.0018%.

[0062] In this specification, REM refers to one or more elements selected from the group consisting of scandium (Sc), atomic number 21; yttrium (Y), atomic number 39; and lanthanides, lanthanum (La), atomic number 57 to lutetium (Lu), atomic number 71. In this specification, REM content refers to the total content of these elements.

[0063] [Tensile strength] The tensile strength of the seamless steel pipe according to this embodiment is 900 to 1180 MPa. In this specification, tensile strength refers to the maximum stress during uniform elongation obtained by a tensile test conducted in accordance with JIS Z2241:2011. Provided that the other components of this embodiment are met, the seamless steel pipe according to this embodiment has excellent hydrogen embrittlement resistance even with a tensile strength of 900 to 1180 MPa.

[0064] In this embodiment, the preferred lower limit of the tensile strength is 920 MPa, more preferably 940 MPa, and even more preferably 950 MPa. In this embodiment, the preferred upper limit of the tensile strength is 1160 MPa, more preferably 1140 MPa, and even more preferably 1120 MPa. In this embodiment, the yield strength of the seamless steel pipe is not particularly limited. The yield strength of the seamless steel pipe may be, for example, 862 to 1069 MPa.

[0065] The tensile strength and yield strength of the seamless steel pipe according to this embodiment can be determined by the following method. Specifically, a tensile test specimen is prepared from the seamless steel pipe according to this embodiment using a method compliant with the High Pressure Gas Safety Association standard KHKS 0220 (2020) "Standards for Ultra-High Pressure Gas Equipment". More specifically, the tensile test specimen is a round bar tensile test specimen, and the axis of the round bar tensile test specimen is prepared so that it coincides with the position of wall thickness t / 4 on the outer surface side of the seamless steel pipe. Here, the position of wall thickness t / 4 on the outer surface side of the steel pipe means the position at a depth of t / 4 from the outer surface of the steel pipe, where the wall thickness of the steel pipe is t. In this case, the round bar tensile test specimen has a parallel section diameter of 8.0 mm and a parallel section length of 56 mm. The axial direction of the round bar tensile test specimen is perpendicular to the pipe axis direction and pipe diameter direction of the steel pipe. If a round bar tensile test specimen cannot be prepared from the steel pipe, an arc-shaped test specimen is prepared. The dimensions of the arc-shaped test specimen are, for example, the total thickness, with a width of 25.4 mm and a gauge length of 50.8 mm.

[0066] Tensile tests are conducted using the prepared tensile specimens at room temperature (25°C) in air, in accordance with JIS Z2241:2011. The maximum stress (MPa) in uniform elongation obtained from the tensile test is defined as the tensile strength. The 0.2% offset proof stress (MPa) obtained from the tensile test is defined as the yield strength. Both the tensile strength (MPa) and the yield strength (MPa) are calculated by rounding the obtained values ​​to the first decimal place.

[0067] [Number density of coarse aluminum oxide] The seamless steel pipe according to this embodiment, assuming the above-mentioned chemical composition and tensile strength of 900-1180 MPa, has a number density of 40 coarse Al oxides / 200 mm 2 It is less than [a certain value]. As stated above, in this specification, particles with an Al content of 20% or more by mass and an O content of 10% or more are also referred to as "Al oxides". As stated above, in this specification, Al oxides with a major axis of 5.0 μm or more are also referred to as "coarse Al oxides". In other words, coarse Al oxides mean particles with an Al content of 20% or more by mass, an O content of 10% or more by mass, and a major axis of 5.0 μm or more.

[0068] As described above, when manufacturing seamless steel pipes having the above-mentioned chemical composition, deoxidation is mainly carried out with aluminum (Al) during the steelmaking process. Therefore, a large number of Al oxides tend to form in seamless steel pipes having the above-mentioned chemical composition. Furthermore, Al oxides are hard oxides, and there is a concern that they will reduce the hydrogen embrittlement resistance of the seamless steel pipe. In particular, when the tensile strength is high, such as 900 MPa or more, the effect of coarse Al oxides tends to become apparent, and the hydrogen embrittlement resistance tends to decrease significantly. Therefore, in the seamless steel pipe according to this embodiment having the above-mentioned chemical composition and a tensile strength of 900 to 1180 MPa, the number density of coarse Al oxides is set to 40 particles / 200 mm 2 Less than.

[0069] In this embodiment, the preferred upper limit for the number density of coarse Al oxide is 39 particles / 200 mm². 2 And more preferably 38 pieces / 200mm 2 And more preferably 37 pieces / 200mm 2 In this embodiment, the lower limit of the number density of coarse Al oxide is not particularly limited, and is 0 particles / 200 mm. 2 This may also be the case. The lower limit of the number density of coarse Al oxide is, for example, 5 particles / 200 mm. 2 It may also be 10 pieces / 200mm 2 It may also be 15 pieces / 200mm 2 That's fine.

[0070] In this embodiment, the number density of coarse Al oxides in the seamless steel pipe can be determined by the following method. First, a test specimen is prepared from the center of the wall thickness of the seamless steel pipe according to this embodiment, with an observation surface that includes both the axial direction and the radial direction of the pipe. Here, the area of ​​the observation surface is not limited, but for example, 300 mm 2 (20mm x 15mm). Furthermore, the size of the test specimen is not particularly limited as long as the above observation surface is obtained.

[0071] After polishing the observation surface of the prepared test specimen to a mirror finish, measurements are taken. The number of Al oxide particles with a major axis of 5.0 μm or larger is determined on the observation surface. Specifically, first, particles on the observation surface are identified based on contrast. Elemental concentration analysis (EDS analysis) is performed on each identified particle. In the EDS analysis, the acceleration voltage is set to 20 kV, and the target elements are quantified as N, O, Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Cu, Zr, and Nb. Based on the EDS analysis results for each particle, if the Al content is 20% or more by mass and the O content is 10% or more, that particle is identified as "Al oxide".

[0072] From the Al oxides identified on the observation surface, Al oxides with a major axis of 5.0 μm or more (coarse Al oxides) are identified, and the total number of coarse Al oxides is determined. The major axis of Al oxides can be determined by well-known methods. In this specification, the major axis of Al oxide refers to the longest line segment connecting any two points on the outer circumference of the Al oxide on the observation surface.

[0073] Based on the total number of coarse Al oxide particles and the total area of ​​the observation surface, the number density of coarse Al oxide particles (particles / 200mm²) is calculated. 2 ) is determined. In this embodiment, the number density of coarse Al oxide (pieces / 200mm) is calculated. 2 The result is obtained by rounding the obtained value to the first decimal place. Furthermore, the number density of coarse Al oxide can be measured using a scanning electron microscope equipped with a compositional analysis function (SEM-EDS instrument). For example, the automated analyzer manufactured by FEI (ASPEX), product name: Metals Quality Analyzer, can be used as a SEM-EDS instrument.

[0074] [Residual stress on the inner surface] The seamless steel pipe according to this embodiment has the above-mentioned chemical composition and a tensile strength of 900 to 1180 MPa, and the number density of coarse Al oxide is 40 particles / 200 mm 2Assuming the following conditions are met, the residual stress on the inner surface of the seamless steel pipe is -50 MPa or less. As a result, the seamless steel pipe according to this embodiment can achieve both a tensile strength of 900 to 1180 MPa and excellent resistance to hydrogen embrittlement.

[0075] As described above, when the residual stress on the inner surface of a seamless steel pipe is -50 MPa or less, compressive residual stress is present on the inner surface of the seamless steel pipe. In this case, due to the balance of internal stresses, regions with tensile residual stress are also formed inside the seamless steel pipe. On the other hand, it is thought that regions with tensile residual stress may actually promote crack propagation. However, when a strong compressive residual stress of -50 MPa or less is present inside the seamless steel pipe, this layer with strong compressive residual stress may effectively suppress crack propagation. As a result, crack propagation may be suppressed throughout the entire seamless steel pipe due to the influence of the regions with compressive residual stress. Consequently, crack propagation may be suppressed, potentially improving hydrogen embrittlement resistance. Therefore, in the seamless steel pipe according to this embodiment, the residual stress on the inner surface is set to -50 MPa or less.

[0076] In this embodiment, the preferred upper limit of the residual stress on the inner surface of the seamless steel pipe is -60 MPa, more preferably -80 MPa, even more preferably -100 MPa, and even more preferably -120 MPa. In this embodiment, the lower limit of the residual stress on the inner surface of the seamless steel pipe is not particularly limited and may be -300 MPa. The lower limit of the residual stress on the inner surface of the seamless steel pipe may be, for example, -280 MPa, -260 MPa, or -240 MPa.

[0077] In the seamless steel pipe according to this embodiment, the residual stress on the outer surface is not particularly limited. In seamless steel pipes intended for use in sour environments or as high-pressure hydrogen containers, the inner surface is particularly susceptible to the effects of hydrogen. Therefore, the residual stress on the inner surface should be -50 MPa or less. However, in the process of reducing the residual stress on the inner surface to -50 MPa or less, it is possible that the residual stress on the outer surface may also become -50 MPa or less. In other words, in the seamless steel pipe according to this embodiment, the residual stress on the outer surface may be -50 MPa or less.

[0078] The upper limit of the residual stress on the outer surface of the seamless steel pipe according to this embodiment may be -60 MPa, -80 MPa, -100 MPa, or -120 MPa. The lower limit of the residual stress on the outer surface of the seamless steel pipe according to this embodiment may be -300 MPa, -280 MPa, -260 MPa, or -240 MPa.

[0079] Here, if the residual stress on the inner surface of the seamless steel pipe is -50 MPa or less, the residual stress is thought to have a gradient in the diameter direction (wall thickness direction), and the residual stress gradually increases from the inner surface toward the center of the wall thickness. In other words, it is highly likely that the residual stress is higher near the center of the wall thickness of the seamless steel pipe. However, as mentioned above, the residual stress on the outer surface of the seamless steel pipe according to this embodiment is not particularly limited. Therefore, the residual stress in the center of the wall thickness is not necessarily the highest in the seamless steel pipe according to this embodiment.

[0080] However, if the residual stress on the outer surface of the seamless steel pipe is -50 MPa or less, and the residual stress on the inner surface and the outer surface of the seamless steel pipe are approximately the same, the residual stress in the center of the wall thickness of the seamless steel pipe will be 50 MPa or more. In this case, the lower limit of the residual stress in the center of the wall thickness of the seamless steel pipe may be 60 MPa, 80 MPa, 100 MPa, or 120 MPa. In this case, the upper limit of the residual stress in the center of the wall thickness of the seamless steel pipe may be 300 MPa, 280 MPa, 260 MPa, or 240 MPa.

[0081] In this embodiment, the residual stress of the seamless steel pipe can be determined by a method in accordance with the method described in Japanese Patent Application Publication No. 2015-184118 (Patent Document 4). Specifically, a measurement hole is drilled into the seamless steel pipe. At this time, the measurement hole is positioned parallel to the diameter direction of the seamless steel pipe. After measuring the inner diameter of the measurement hole with an air probe, the residual stress is released by trepanning (electrical discharge machining). The inner diameter of the measurement hole is measured after trepanning. The residual stress at that position can be determined from the difference in the inner diameter of the measurement hole before and after trepanning. The residual stress is obtained by rounding the obtained value to the first decimal place.

[0082] Furthermore, the method described above, in principle, cannot measure residual stress in the surface layer up to a depth of 1 mm from the surface of the steel material. Therefore, in this embodiment, the residual stress on the inner surface of a seamless steel pipe refers to the residual stress at a position 1 mm from the inner surface of the seamless steel pipe in the wall thickness direction (pipe diameter direction). Moreover, in this embodiment, residual stress refers to residual stress in the pipe diameter direction. In this embodiment, the residual stress on the inner surface of a seamless steel pipe refers to the residual stress in the pipe diameter direction measured by a deep hole drilling method that takes into account plastic deformation due to processing during measurement, at a position 1 mm from the inner surface of the seamless steel pipe in the pipe diameter direction.

[0083] Similarly, in this embodiment, the residual stress on the outer surface of the seamless steel pipe refers to the residual stress in the diameter direction measured by a deep-hole drilling method that takes into account plastic deformation due to processing during measurement, at a position 1 mm from the outer surface of the seamless steel pipe in the wall thickness direction (pipe diameter direction). Similarly, in this embodiment, the residual stress at the center of the wall thickness of the seamless steel pipe refers to the residual stress in the diameter direction measured by a deep-hole drilling method that takes into account plastic deformation due to processing during measurement, at the center of the wall thickness of the seamless steel pipe.

[0084] [Hydrogen embrittlement resistance] The seamless steel pipe according to this embodiment has the above-mentioned chemical composition and a tensile strength of 900 to 1180 MPa, and the number density of coarse Al oxide is 40 particles / 200 mm 2 The residual stress on the inner surface of the seamless steel pipe is less than -50 MPa. As a result, the seamless steel pipe according to this embodiment can achieve both a tensile strength of 900 to 1180 MPa and excellent hydrogen embrittlement resistance. In this embodiment, having excellent hydrogen embrittlement resistance is defined as follows.

[0085] In this embodiment, the hydrogen embrittlement resistance was determined by a rising load test conducted in accordance with the High Pressure Gas Safety Association standard KHKS 0220 (2020) "Standards for Ultra-High Pressure Gas Equipment", using the lower limit stress intensity factor K. 1H The evaluation is based on the value (MPa√m). Specifically, rising load test specimens are prepared from the seamless steel pipe according to this embodiment in accordance with KHKS 0220 (2020). More specifically, rising load test specimens are prepared so that the surface of the test specimen is 2 mm from the inner surface in the wall thickness direction of the seamless steel pipe. In this case, the load application axis direction of the test specimen is also perpendicular to the pipe axis direction and pipe diameter direction. Furthermore, fatigue pre-cracks in the rising load test specimen are introduced with the aim of reaching 3 mm.

[0086] The rising load test will be conducted at room temperature in both an atmospheric environment and a hydrogen gas environment at 90 MPa. The test speed will be the load line opening displacement speed of 2 × 10⁻¹⁰. -3The load is set to mm / sec, and the opening displacement is measured with a clip gauge. The lower limit stress intensity factor K is calculated using the load at the initiation point of hydrogen-induced crack propagation and the fatigue pre-crack length obtained from fracture surface measurements. 1H The value (MPa√m) is determined. The starting point of hydrogen-induced cracking is determined by superimposing the load-opening displacement curves for the atmospheric environment and the hydrogen gas environment. In this embodiment, the lower limit stress intensity factor K is used. 1H The value (MPa√m) is obtained by rounding the resulting number to the nearest tenth.

[0087] In this embodiment, the lower limit stress intensity factor K obtained under the above conditions 1H If the value is 40 MPa√m or higher, the seamless steel pipe is judged to have excellent hydrogen embrittlement resistance.

[0088] [Microorganisms] In the microstructure of the seamless steel pipe according to this embodiment, the total area ratio of tempered martensite and tempered bainite is 90% or more. The remainder of the microstructure is, for example, ferrite and / or pearlite. In this embodiment, if the seamless steel pipe has the above-mentioned chemical composition and a tensile strength of 900 to 1180 MPa, it can be determined that the total area ratio of tempered martensite and tempered bainite is 90% or more.

[0089] [Method for measuring the total area ratio of tempered martensite and tempered bainite] The total area ratio of tempered martensite and tempered bainite in the microstructure of the seamless steel pipe according to this embodiment can also be determined by the following method. Specifically, a test specimen is prepared from the seamless steel pipe, which includes the central position of the wall thickness, the area to be observed, and has an observation surface parallel to the pipe axis direction. The size of the test specimen is not particularly limited. For example, the size of the test specimen is 10 mm in the pipe axis direction × 5 mm in the pipe circumferential direction × 10 mm in the pipe diameter direction. The pipe circumferential direction corresponds to the direction perpendicular to the pipe axis direction and the pipe diameter direction (wall thickness direction). Furthermore, the surface including the pipe axis direction and the pipe diameter direction (a 10 mm × 10 mm surface in the case of the test specimen size described above) is used as the observation surface.

[0090] After polishing the observation surface of the test specimen to a mirror finish, it is immersed in Nital etching solution for about 10 seconds to reveal the microstructure by etching. Ten arbitrary fields of view within the observation area of ​​the etched observation surface are observed as secondary electron images using a scanning electron microscope (SEM). The area of ​​each of the ten fields of view within the observation area is, for example, 400 μm. 2 (Magnification 5000x).

[0091] In each field of view, tempered martensite and tempered bainite are identified. In each field of view, tempered martensite and tempered bainite can be distinguished from other tissues (ferrite, pearlite, etc.) based on their morphology. Specifically, tissues with lamellar structure can be identified as pearlite. Tissues containing lath or lenses can be identified as tempered martensite and tempered bainite. Tissues without substructure within the grains can be identified as ferrite.

[0092] The total area ratio of the identified tempered martensite and tempered bainite is determined. The method for determining the total area ratio is not particularly limited and may be a well-known method. For example, the total area ratio of tempered martensite and tempered bainite can be determined by image analysis. In this embodiment, the arithmetic mean of the total area ratios of tempered martensite and tempered bainite obtained in all fields (10 fields) is defined as the total area ratio of tempered martensite and tempered bainite (%).

[0093] [Applications of seamless steel pipes] Preferably, the seamless steel pipe of this embodiment is one of the following: a seamless steel pipe for oil wells, a seamless steel pipe for line pipes, or a seamless steel pipe for high-pressure hydrogen containers. A seamless steel pipe for oil wells means a seamless steel pipe for oil well tubing applications. Oil well tubing includes, for example, casings, tubing, drill pipes, etc., used for drilling oil or gas wells, extracting crude oil or natural gas, etc. A seamless steel pipe for line pipes means a seamless steel pipe for line pipe applications that constitute a pipeline for transporting production fluid (crude oil or natural gas) extracted from an oil or gas well. A pipeline includes, for example, a flow line that transports production fluid from an oil or gas well, a gathering line that collects the production fluid transported by the flow line and transports it to a primary processing facility, a trunk line that transports the production fluid, which has undergone primary processing such as dewatering, to the vicinity of the market, and a distribution line that transports it to consumers. Seamless steel pipes for high-pressure hydrogen containers are standardized in ISO 11439, ANSI / NGV, the High-Pressure Gas Safety Act, the Container Safety Regulations Exemplary Standards, etc., and refer to seamless steel pipes used in high-pressure hydrogen containers that store high-pressure hydrogen gas. The seamless steel pipe according to this embodiment may be a seamless steel pipe for high-pressure hydrogen containers, a seamless steel pipe for high-pressure hydrogen accumulators, or a seamless steel pipe for high-pressure hydrogen cylinders.

[0094] [Manufacturing method] The following describes an example of a method for manufacturing seamless steel pipes according to this embodiment. Note that the manufacturing method described below is just one example, and the method for manufacturing seamless steel pipes according to this embodiment is not limited to this example. In other words, as long as a seamless steel pipe having the above-described configuration can be manufactured according to this embodiment, the method is not limited to the method described below. However, the manufacturing method described below is a preferred method for manufacturing seamless steel pipes according to this embodiment.

[0095] An example of a manufacturing method for seamless steel pipes according to this embodiment includes a material manufacturing process, a hot working process, and a heat treatment process. Each process will be described below.

[0096] [Material manufacturing process] In the material manufacturing process, the material is manufactured using molten steel having the chemical composition described above. In this embodiment, the material is preferably a billet. The method of casting the molten steel is not particularly limited, but for example, it is a continuous casting method. In this case, the billet may be manufactured by a continuous casting method, or the billet may be manufactured by performing a bloc rolling on a bloom or billet manufactured by a continuous casting method. When casting molten steel by a continuous casting method, it is preferable to carry it out in the following manner.

[0097] The casting speed in a continuous casting machine is preferably 1.0 to 3.0 m / min. If the casting speed is too slow, accumulation zones of Al oxide may form in the material. In this case, the manufactured seamless steel pipe will contain a large amount of coarse Al oxide, and the hydrogen embrittlement resistance of the seamless steel pipe will decrease. On the other hand, if the casting speed is too fast, the Al oxide may not be able to float to the surface, and a large amount of Al oxide may remain in the material. In this case, the manufactured seamless steel pipe will contain a large amount of coarse Al oxide, and the hydrogen embrittlement resistance of the seamless steel pipe will decrease. Therefore, the casting speed in a continuous casting machine is preferably 1.0 to 3.0 m / min.

[0098] When manufacturing the material by continuous casting, it is preferable to further electromagnetically stir the molten steel within the mold. Specifically, by performing electromagnetic stirring within the mold at a current value of 330 to 450 A, it becomes less likely for Al oxide accumulation zones to form in the material. If the current value for electromagnetic stirring within the mold is too low, the stirring of the molten steel will be insufficient, and Al oxide accumulation zones may form in the material. In this case, the manufactured seamless steel pipe will contain a large amount of coarse Al oxide, and the hydrogen embrittlement resistance of the seamless steel pipe will decrease. On the other hand, if the current value for electromagnetic stirring within the mold is too high, the manufacturing equipment may be overloaded. Therefore, in this embodiment, it is preferable to set the current value for electromagnetic stirring within the mold to 330 to 450 A.

[0099] [Hot working process] In the hot working process, the prepared material (billet) is hot-worked to produce intermediate steel material (raw pipe). First, the billet is heated in a heating furnace. The heating temperature is not particularly limited, but for example, it is 1100 to 1300°C. Hot working is performed on the billet removed from the heating furnace to produce raw pipe (seamless steel pipe). The method of hot working is not particularly limited and any well-known method may be used.

[0100] For example, the Mannesmann process may be used as a hot working method to produce the raw pipe. In this case, a round billet is perforated and rolled using a perforating machine. When perforating and rolling, the perforation ratio is not particularly limited, but for example, it is 1.0 to 4.0. The perforated and rolled round billet is further hot-rolled using a mandrel mill, reducer, sizing mill, etc., to produce the raw pipe. The raw pipe may also be produced from the billet using other hot working methods. For example, if the seamless steel pipe is a short, thick-walled seamless steel pipe such as a coupling, the raw pipe may be produced by forging using the Erhardt process or similar methods. The raw pipe is produced by the above process. The wall thickness of the raw pipe is not particularly limited, but for example, it is 9 to 60 mm.

[0101] Raw tubes manufactured by hot working may be air-cooled (as-rolled). Raw tubes manufactured by hot working may be quenched directly after hot working without cooling to room temperature, or they may be reheated after hot working before quenching. When quenching is performed directly after hot working or after reheating, cooling may be stopped or slowed down during quenching. In this case, the occurrence of quench cracks in the raw tube can be suppressed. When quenching is performed directly after hot working or after reheating, stress relief annealing (SR) may be performed after quenching but before the next heat treatment process. In this case, residual stress in the raw tube is removed.

[0102] [Heat treatment process] The heat treatment process according to this embodiment includes a quenching step and a tempering step. Each step will be described below.

[0103] [Heat treatment process] In the quenching process, the raw tube is subjected to quenching. Quenching is carried out by a well-known method. In this specification, "quenching" means rapidly cooling the raw tube above its A3 transformation point. Here, the quenching temperature in quenching refers to the temperature of the raw tube when it is rapidly cooled. When the raw tube is held in a heating furnace or supplemental heating furnace and then rapidly cooled, the quenching temperature corresponds to the temperature of the heat treatment furnace in which it is held. In this case, the time from when the temperature of the raw tube reaches a predetermined holding temperature until it is removed from the heat treatment furnace is also called the holding time in quenching.

[0104] The preferred quenching temperature is 900 to 950°C. If the holding temperature is too high, the prior γ grains may coarseen, and excellent hydrogen embrittlement resistance may not be obtained. On the other hand, if the quenching temperature is too low, the desired microstructure may not be obtained, and the desired mechanical properties may not be achieved. Therefore, a quenching temperature of 900 to 950°C is preferred. The holding time is not particularly limited, but for example, it is 10 to 60 minutes.

[0105] The quenching method involves continuously cooling the raw tube from the quenching temperature, thereby continuously lowering the surface temperature of the raw tube. The method of continuous cooling is not particularly limited and any well-known method may be used. Examples of continuous cooling methods include immersing the raw tube in a water bath or accelerating the cooling of the raw tube by shower water cooling or mist cooling.

[0106] [Tempering process] In the tempering process, the raw tube that has undergone the above-described quenching is tempered. In this specification, "tempering" refers to the process of tempering the raw tube after quenching. c1 This means reheating and holding the material at a temperature below its transformation point. Here, the holding temperature in tempering corresponds to the temperature of the heat treatment furnace when the raw tube is heated and held after quenching. The holding time in tempering refers to the time from when the temperature of the raw tube reaches the predetermined holding temperature until it is removed from the heat treatment furnace.

[0107] The holding temperature during tempering is adjusted appropriately according to the chemical composition of the steel material and the tensile strength to be obtained. In other words, for a raw pipe having the chemical composition of this embodiment, the holding temperature and holding time are adjusted to adjust the tensile strength of the seamless steel pipe to 900 to 1180 MPa. In the tempering process according to this embodiment, the preferred holding temperature is 650 to 690°C, and the preferred holding time is 15 to 180 minutes.

[0108] In the tempering process according to this embodiment, the raw tube is rapidly cooled after being extracted from the heat treatment furnace. By rapidly cooling the raw tube, the inner surface of the raw tube partially shrinks, and the residual stress on the inner surface of the raw tube can be reduced to -50 MPa or less.

[0109] Therefore, in this embodiment, during the cooling process in the tempering step, the cooling stop temperature is set to 100°C or lower, and the average cooling rate between 500°C and 100°C is set to 25°C / second or higher. If the cooling stop temperature is too high, the residual stress on the inner surface of the raw tube may not be sufficiently reduced. On the other hand, if the cooling stop temperature is 100°C or lower, the residual stress on the inner surface of the raw tube can be stably reduced to -50 MPa or lower. The lower limit of the cooling stop temperature is not particularly limited, but for example, it is room temperature (25°C).

[0110] Furthermore, if the average cooling rate between 500 and 100°C is too slow, the residual stress on the inner surface of the raw tube may not be sufficiently reduced. On the other hand, if the average cooling rate between 500 and 100°C is 25°C / second or higher, the residual stress on the inner surface of the raw tube can be stably reduced to -50 MPa or less. There is no particular upper limit to the average cooling rate between 500 and 100°C, but for example, it is 100°C / second.

[0111] Therefore, in this embodiment, it is preferable to set the cooling stop temperature to 100°C or lower and the average cooling rate between 500°C and 100°C to 25°C / second or higher during the tempering process. In this embodiment, the cooling stop temperature for rapid cooling during the tempering process and the average cooling rate between 500°C and 100°C are defined by the temperature measured on the inner surface of the seamless steel pipe.

[0112] In the tempering process according to this embodiment, the method of rapidly cooling the raw pipe is not particularly limited, but immersion in a water tank is preferred. As described above, in this embodiment, the residual stress on the inner surface of the seamless steel pipe is reduced by rapidly cooling the inner surface of the seamless steel pipe. In this case, for example, shower water cooling of the outer surface of the raw pipe may not be able to effectively rapidly cool the inner surface of the raw pipe. Therefore, in the rapid cooling process during the tempering, it is preferable to immerse the raw pipe in a water tank and generate a water flow inside the raw pipe to rapidly cool it.

[0113] By carrying out the above manufacturing process, a seamless steel pipe according to this embodiment can be manufactured. However, as stated above, the above manufacturing method is just one example, and it may be manufactured by other manufacturing methods. The effects of the seamless steel pipe according to this embodiment will be explained in more detail below with reference to examples. However, the various conditions in the examples described below are just one example of conditions adopted to confirm the feasibility and effects of the seamless steel pipe according to this embodiment. Therefore, the seamless steel pipe according to this embodiment is not limited to the one example of conditions described in the examples. [Examples]

[0114] Molten steel having the chemical compositions shown in Tables 1A and 1B was produced. In Table 1B, "-" indicates that the content of each element is at an impurity level. Specifically, the Cu, Ni, and W content of steel A was 0%, rounded to the third decimal place. Furthermore, the Zr, Ca, Mg, and rare earth element (REM) content of steel A was 0%, rounded to the fifth decimal place.

[0115] [Table 1A]

[0116] [Table 1B]

[0117] Round billets were manufactured using the molten steel described above by continuous casting. In the continuous casting method, the molten steel was cast into round billets at the casting speeds shown in Table 2. At this time, electromagnetic stirring was performed inside the mold at the current values ​​shown in Table 2.

[0118] [Table 2]

[0119] After heating the round billets of each test number to 1250°C, hot rolling was performed using the Mannesmann-mandrel method to produce the raw pipes (seamless steel pipes) of each test number. From the produced raw pipes, arc-shaped test specimens of a size suitable for producing test pieces to be used in the evaluation tests described later were prepared.

[0120] Each test specimen with the obtained test number was subjected to quenching. Specifically, each test specimen with the test number was held for 10 minutes at the temperature indicated in the "Quenching Temperature (°C)" column of Table 2, and then quenched by shower water cooling. The quenching temperature (°C) indicated in Table 2 is the temperature (°C) of the heat treatment furnace in which the test specimen was heated.

[0121] Tempering was performed on the test specimens for each test number that had undergone quenching. Specifically, the test specimens for each test number were tempered by holding them for 60 minutes at the temperature indicated in the "Tempering Temperature (°C)" column of Table 2. The tempering temperature (°C) indicated in Table 2 refers to the temperature (°C) of the tempering furnace in which the test specimens were heated. Furthermore, the test specimens for each test number that had been tempered were rapidly cooled by immersion in a water bath. At this time, for test numbers where the cooling stop temperature was 100°C or lower, "A (Acceptable)" is indicated in the "Cooling Stop Temperature (°C)" column of Table 2. For these test numbers, the average cooling rate (°C / sec) between 500 and 100°C is indicated in the "Average Cooling Rate (°C / sec)" column of Table 2. In addition, for test numbers where the cooling stop temperature exceeded 100°C, the temperature at which cooling stopped is indicated in the "Cooling Stop Temperature (°C)" column of Table 2. For these test numbers, the average cooling rate (°C / sec) from 500°C to the cooling stop temperature is shown in the "Average Cooling Rate (°C / sec)" column of Table 2. In this example, the cooling stop temperature and average cooling rate were determined from the temperature measured at a position corresponding to the inner surface of the seamless steel pipe in the test material.

[0122] [Evaluation Test] The test specimens for each test number were obtained through the manufacturing process described above. Tensile tests, coarse Al oxide number density tests, residual stress tests, and rising load tests were performed on the test specimens for each test number.

[0123] [Tensile test] Tensile tests were performed on the specimens for each test number using the method described above to determine the tensile strength and yield strength. Specifically, round bar tensile test specimens were prepared from the specimens for each test number using a method compliant with KHKS 0220 (2020). The round bar tensile test specimens had a parallel section diameter of 8.0 mm and a parallel section length of 56.0 mm. A specific position was designated on the specimen corresponding to the wall thickness t / 4 on the outer surface side of the seamless steel pipe, and the axial direction of the round bar tensile test specimen was perpendicular to the pipe axis direction and pipe diameter direction of the seamless steel pipe. Using the prepared round bar tensile test specimens, tensile tests were performed at room temperature (25°C) in air compliant with JIS Z2241:2011, and the maximum stress in the uniform elongation obtained was defined as the tensile strength (MPa). The 0.2% offset proof stress (MPa) obtained in a similar tensile test was defined as the yield strength. The obtained tensile strengths for the specimens for each test number are shown in Table 3 as "TS (MPa)". Furthermore, for all test numbers except test number 35, the yield strength of the test material was within the range of 862 to 1069 MPa.

[0124] [Table 3]

[0125] [Number density measurement test of coarse aluminum oxide] For each test specimen, the number density measurement test for coarse Al oxide was performed using the method described above to determine the number density of Al oxide with a major axis of 5.0 μm or larger (coarse Al oxide). The number density of coarse Al oxide was determined using the method described above, with test specimens prepared from the center of the thickness of each test specimen. The obtained number density of coarse Al oxide (pieces / 200 mm) was calculated. 2 ) are shown in Table 3 as "Coarse Al oxide (pieces / 200mm)". 2 This is shown in the ")" column.

[0126] [Residual stress measurement test] For each test specimen, a residual stress measurement test was performed using the method described above to determine the residual stress. A measurement hole was drilled in the diameter direction of the seamless steel pipe, penetrating through each test specimen. After measuring the inner diameter of the measurement hole with an air probe, the residual stress was released by trepanning. Furthermore, the inner diameter of the measurement hole was measured after trepanning. The residual stress was determined from the difference in the inner diameter of the measurement hole before and after trepanning. In this embodiment, for each test specimen, the residual stress in the diameter direction at a position 1 mm from the inner surface in the diameter direction of the seamless steel pipe was defined as the residual stress at the inner surface (MPa). Similarly, for each test specimen, the residual stress in the diameter direction at a position 1 mm from the outer surface in the diameter direction of the seamless steel pipe was defined as the residual stress at the outer surface (MPa). Similarly, for each test number, the residual stress in the radial direction at the center of the wall thickness of the seamless steel pipe was defined as the residual stress at the center of the wall thickness (MPa). The obtained residual stress (MPa) on the inner surface is shown in the "Inner Surface" column of the "Residual Stress (MPa)" column in Table 3. Similarly, the obtained residual stress (MPa) at the center of the wall thickness is shown in the "Center of Wall Thickness" column of the "Residual Stress (MPa)" column in Table 3. Similarly, the obtained residual stress (MPa) on the outer surface is shown in the "Outer Surface" column of the "Residual Stress (MPa)" column in Table 3.

[0127] [Rising Road Test] For each test specimen, a rising load test was performed using the method described above to evaluate its hydrogen embrittlement resistance. Specifically, rising load specimens were prepared from each test specimen in accordance with KHKS 0220 (2020). Specifically, the rising load specimens were prepared so that the surface of the specimen was located 2 mm in the wall thickness direction from the position corresponding to the inner surface of the seamless steel pipe. In this case, the load-applying axis direction of the specimen was also set perpendicular to the pipe axis direction and pipe diameter direction of the seamless steel pipe. A 3 mm fatigue precrack was introduced into the prepared rising load specimens.

[0128] For each test numbered rising load test specimen, a rising load test was performed at room temperature in both an atmospheric environment and a 90 MPa hydrogen gas environment, in accordance with KHKS 0220 (2020). The test speed was 2 × 10⁻¹⁰ load line opening displacement speed. -3 The load was set to mm / sec, and the opening displacement was measured with a clip gauge. The lower limit stress intensity factor K was calculated using the load at the initiation point of hydrogen-induced crack propagation and the fatigue pre-crack length obtained from fracture surface measurements. 1H The value (MPa√m) was calculated. The obtained lower limit stress intensity factor K 1H The values ​​(MPa√m) are shown in Table 3.

[0129] [Evaluation Results] Referring to Tables 1A, 1B, 2, and 3, the test specimens for test numbers 1 to 17 had the chemical composition described above and were manufactured under the preferred manufacturing conditions described above. As a result, these test specimens had a tensile strength of 900 to 1180 MPa and a number density of 40 coarse Al oxide particles / 200 mm². 2 The value was less than -50 MPa, and the residual stress on the inner surface of the seamless steel pipe was -50 MPa or less. As a result, these test materials had a lower limit stress intensity factor K 1H The values ​​were 40 MPa√m or higher, indicating excellent resistance to hydrogen embrittlement. In other words, these test materials possessed both high strength and excellent resistance to hydrogen embrittlement. Furthermore, in the microstructure of test materials 1 to 17, it was determined that the total area ratio of tempered martensite and tempered bainite was 90% or higher.

[0130] On the other hand, the test material for test number 18 had too low a Mo content. As a result, this test material had a lower limit stress intensity factor K 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0131] The material used in test number 19 had too high a sulfur content. As a result, this material had a lower limit stress intensity factor of K. 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0132] The test material for test number 20 had too high an oxygen content. As a result, this test material had a number density of 40 coarse aluminum oxide particles per 200 mm³. 2 The above is the result. As a result, the lower limit stress intensity factor K of this test material 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0133] The test material for test number 21 had too low a Cr content, too low a Mo content, and too high a Ti content. As a result, this test material had a lower limit stress intensity factor K 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0134] The material used in test number 22 had too high a manganese content. As a result, this material had a lower limit stress intensity factor K 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0135] The casting speed in continuous casting was too slow for test materials numbered 23-26. As a result, these test materials had a number density of 40 coarse Al oxide particles per 200 mm³. 2 The above is the result. As a result, these test materials had a lower limit stress intensity factor K 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0136] The average cooling rate during the tempering process of test material number 27 was too slow. As a result, the residual stress on the inner surface of this seamless steel pipe exceeded -50 MPa. Consequently, the lower limit stress intensity factor K of this material... 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0137] The test materials for test numbers 28-31 were cast at too slow a rate during continuous casting, and the average cooling rate during the tempering process was too slow. As a result, these test materials had a number density of 40 coarse Al oxide particles per 200 mm³. 2As a result, the residual stress on the inner surface of the seamless steel pipe exceeded -50 MPa. Consequently, these test materials had a lower limit stress intensity factor K 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0138] In test specimens 32-34, the cooling stop temperature during the tempering process was too high. As a result, the residual stress on the inner surface of these seamless steel pipes exceeded -50 MPa. Consequently, these specimens had a lower limit stress intensity factor K 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0139] The tempering temperature of test material No. 35 was too low during the tempering process. As a result, the tensile strength of this material exceeded 1180 MPa. Consequently, the lower limit stress intensity factor K of this material was 1H The value was less than 40 MPa√m, indicating that it did not possess excellent hydrogen embrittlement resistance.

[0140] The embodiments of this disclosure have been described above. However, the embodiments described above are merely examples for implementing this disclosure. Therefore, this disclosure is not limited to the embodiments described above, and the embodiments described above can be modified as appropriate without departing from the spirit of this disclosure.

Claims

1. It is a seamless steel pipe, The chemical composition is expressed in mass percent. C: 0.15-0.45%, Si: 0.05-1.00%, Mn: 0.05-0.50%, P: 0.030% or less, S: 0.0050% or less, Cr: 0.30-1.20%, Mo: 0.50-2.00%, Ti: 0.002 to 0.020%, Nb: 0.002 to 0.100%, V: 0.05-0.30%, B: 0.0005-0.0040%, Al: 0.005-0.100%, N: 0.0100% or less, O: Less than 0.0040%, Cu: 0 to 0.50%, Ni: 0 to 0.50%, W: 0-0.50%, Zr: 0 to 0.0100%, Ca: 0-0.0100%, Mg: 0 to 0.0100%, Rare earth elements: 0-0.0100%, and The remainder consists of Fe and impurities. The tensile strength is 900 to 1180 MPa. In the aforementioned seamless steel pipe, In mass%, the Al content is 20% or more, the O content is 10% or more, and the number density of Al oxide particles with a major axis of 5.0 μm or more is 40 particles / 200 mm. 2 It is less than, On the inner surface of the aforementioned seamless steel pipe, the residual stress is -50 MPa or less. Seamless steel pipe.

2. A seamless steel pipe according to claim 1, The aforementioned chemical composition is Cu: 0.01 to 0.50%, Ni: 0.01-0.50%, W: 0.01-0.50%, Zr: 0.0001 to 0.0100%, Ca: 0.0001-0.0100%, Mg: 0.0001 to 0.0100%, and, Contains one or more elements selected from the group consisting of rare earth elements: 0.0001 to 0.0100%. Seamless steel pipe.

3. A seamless steel pipe according to claim 1 or claim 2, The aforementioned seamless steel pipe is one of the following: a seamless steel pipe for oil wells, a seamless steel pipe for line pipes, or a seamless steel pipe for high-pressure hydrogen containers. Seamless steel pipe.

4. A seamless steel pipe according to claim 3, The seamless steel pipe for high-pressure hydrogen containers is either a seamless steel pipe for high-pressure hydrogen accumulators or a seamless steel pipe for high-pressure hydrogen cylinders. Seamless steel pipe.

Citation Information

Patent Citations

  • Low alloy steel for high pressure hydrogen gas environment, and vessel for high pressure hydrogen

    JP2009074122A

  • High-strength seamless steel tube for oil well with excellent resistance to sulfide stress cracking, and method for producing the same

    JP2011246798A

  • High-strength seamless steel pipe with excellent resistance to sulfide stress cracking for oil well and method for producing the same

    JP2015038247A

  • Residual stress measurement method and residual stress measurement device

    JP2015184118A